2020
DOI: 10.1007/jhep02(2020)036
|View full text |Cite
|
Sign up to set email alerts
|

Dark matter bound state formation via emission of a charged scalar

Abstract: The formation of stable or meta-stable bound states can dramatically affect the phenomenology of dark matter (DM). Although the capture into bound states via emission of a vector is known to be significant, the capture via scalar emission suffers from cancellations that render it important only within narrow parameter space. While this is true for neutral scalar mediators, here we show that bound-state formation via emission of a charged scalar can be extremely significant. To this end, we consider DM charged … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
43
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 22 publications
(43 citation statements)
references
References 33 publications
(118 reference statements)
0
43
0
Order By: Relevance
“…Moreover, bound states can form via emission of a Higgs doublet. As we shall see, the cross-sections for BSF via Higgsdoublet emission can exceed those for annihilation or BSF via vector emission by orders of magnitude, and result in a late period of DM chemical recoupling [1]. This, in turn, opens the possibility that thermal-relic WIMP DM may be much heavier than anticipated, JHEP06(2021)124…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…Moreover, bound states can form via emission of a Higgs doublet. As we shall see, the cross-sections for BSF via Higgsdoublet emission can exceed those for annihilation or BSF via vector emission by orders of magnitude, and result in a late period of DM chemical recoupling [1]. This, in turn, opens the possibility that thermal-relic WIMP DM may be much heavier than anticipated, JHEP06(2021)124…”
Section: Introductionmentioning
confidence: 94%
“…Bound states form invariably with dissipation of energy. It has been recently shown that the emission of a scalar boson charged under a symmetry alters the effective Hamiltonian between the interacting particles and gives rise to monopole transitions; this renders bound-state formation (BSF) extremely rapid even for small couplings [1]. For WIMPs, this implies that BSF via emission of a Higgs doublet may be a very significant inelastic process.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, for very heavy DM whose annihilation signals fall outside the energy range of the various telescopes, the low-energy radiation could fall within the energy range probed by telescopes, and could thus be employed to constrain a wider range of DM masses. 2 The radiative BSF cross sections can be comparable to or even significantly larger than the direct annihilation cross sections [4,21,23,24,29,59]. In fact, the BSF cross sections in galactic environments may exceed the so-called canonical annihilation cross section, σv rel ≈ 3 × 10 −26 cm 3 /s, by orders of magnitude due to different reasons.…”
Section: Stable Bound Statesmentioning
confidence: 99%
“…In models that feature co-annihilation between different species and/or non-Abelian forces, a variety of unstable bound states may exist. The formation and decay of unstable bound states diminish the DM density in the early Universe [4], thereby altering the expected DM mass and couplings and affecting all experimental signatures [4,[22][23][24][25][26][27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%